2012
DOI: 10.1097/shk.0b013e31824bcb72
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Elevated Plasma CXCL8 Concentrations Following Red Blood Cell Transfusion in a Trauma Cohort

Abstract: Red blood cell (RBC) transfusion is associated with alterations in systemic concentrations of IL-8/CXCL8 functional homologues in a murine model. Whether RBC transfusion alters systemic neutrophil chemokine concentrations in individuals sustaining traumatic injury is not known. We conducted a retrospective, single-center study of severely injured trauma patients presenting within 12 h of injury with a base deficit > 6 and hypotension in the field. Plasma concentrations of twenty-five chemokines, cytokines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…8 Monocytosis may occur more often than monocytopenia and can occur in combination with extreme prematurity, repeated transfusions of red blood cells, albumin, and theophylline. 21 In syphilis and congenital candidiasis, 22,23 as well as in immune-mediated neutropenia, monocytosis may also occur. 24,25 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…8 Monocytosis may occur more often than monocytopenia and can occur in combination with extreme prematurity, repeated transfusions of red blood cells, albumin, and theophylline. 21 In syphilis and congenital candidiasis, 22,23 as well as in immune-mediated neutropenia, monocytosis may also occur. 24,25 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In the NICU, monocytosis may be seen more frequently than monocytopenia and may occur in association with extreme prematurity, repeated RBC transfusions, albumin infusions, and theophylline therapy. 36 Monocytosis can also be seen in congenital candidiasis and syphilis, 37 , 38 and in immune-mediated neutropenia. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have found nonleukoreduced blood to have proinflammatory effects. 12,27,28 These studies were undertaken in the context of volume resuscitation or in patients undergoing cardiac and orthopedic surgery rather than in a mixed hemodynamically stable critical care population. 29,30 Importantly, these were nonrandomized cohort studies subject to confounding, especially bias by indication.…”
Section: Discussionmentioning
confidence: 99%